Meningkatkan Kemandirian Belajar Siswa Melalui Layanan Bimbingan Kelompok Teknik Home Room - Galuh Hartinah; Aliwanto (JCOSE Jurnal Bimbingan dan Konseling, 2022)
The problem in this study is that students' learning independence is low, the objectives to be achieved in this study in general are to increase student learning independence through home room technique group guidance services, while the specific objectives of this study are to determine: 1) Implementation of home room technique group guidance services room to increase learning independence, 2) Learning independence after participating in the home room technique group guidance service. The method in this study is a quantitative research method, the form of research is in the form of guidance and counseling (PTBK). The results of data analysis from the implementation of home room technique group guidance services in cycle I and cycle II showed that all aspects of learning independence increased, aspects of independent learning attitudes increased by 23.75% from 41.91% to 73.66%, aspects of ability and need in learning increased by 22.5% from 51.97% to 74.47%, in the aspect of future desires and aspirations increased by 20% from 61.28% to 81.28%, aspects of independence and ability in learning increased by 24.5% from 48.65% to 73.15%, and in the last aspect, the aspect of fun activities when studying increased by 15.04% from 55.11% to 70.15%. Overall, there was an increase in student learning independence by 21.16% before being given group guidance actions and after being given home room technique group guidance. Based on these data, it can be concluded that the home room technique group guidance services provided to students can increase learning independence.